The correlation between ART and OCRA methods used for posture assessment of repetitive tasks: correlation between ART and OCRA methods - Jafari Roodbandi, Akram Sadat; Feyzi, Vafa; Foroozanfar, Zohre; Rahimi Moghadam, Somayeh (La Medicina del Lavoro, 2021)
Background and Objective: Repetitive tasks are among the causes of musculoskeletal disorders. Assessment of repetitivetasks is performed through various methods with different scores and significance given to risk factors considered in these methods. Knowing the strengths and weaknesses of each method can contribute to modifying the methods and improving the correlation between them. This study aimed to investigate the correlation between ART and OCRA methods in a career with repetitive movements. Methods: After hierarchical task analysis in a vegetable grower job with repetitive movements, the subtasks were assessed by an assessor who mastered both ART and OCRA methods. The final score of each method was checked using the Pearson correlation coefficient in SPSS 18, after testing the normality of data. Results: Moderate risk levels were reported for 16 out of the 14 sub-tasks analyzed using both methods. In the ART method, 3 sub-tasks and in the OCRA method, 2 sub-tasks had high-risk levels. The Pearson correlation coefficient was 0.842 indicating a moderate correlation between the two posture assessment methods. Conclusion: The findings of the study showed an acceptable correlation and compatibility between the two methods considering the risk levels.